2020
DOI: 10.2147/dddt.s259058
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antiviral Agent Therapy Optimization in Special Populations of COVID-19 Patients</p>

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is now a global outbreak of disease. The antiviral treatment acts as one of the most important means of SARS-CoV-2 infection. Alteration of physiological characteristics in special populations may lead to the change in drug pharmacokinetics, which may result in treatment failure or increased adverse drug reactions. Some potential drugs have shown antiviral effects on SARS-CoV-2 infections, such as chloroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…48 There was a roughly 2.1 fold rise and 6.3 fold rise in the Cmax and AUC, respectively, when favipiravir was given to patients with severe liver dysfunction (Child-Pugh classification C) compared to healthy participants, which warrants a cautious use of favipiravir in patients with liver dysfunction. 48,49 Hypersensitivity reactions, such as rashes, have been reported by 0.5% to <1% of the patients. 48 Previous studies reported that hyperuricemia was not present in the ADE database of WHO, which was used to evaluate ADEs related to favipiravir in the current study.…”
Section: Dovepressmentioning
confidence: 99%
“…48 There was a roughly 2.1 fold rise and 6.3 fold rise in the Cmax and AUC, respectively, when favipiravir was given to patients with severe liver dysfunction (Child-Pugh classification C) compared to healthy participants, which warrants a cautious use of favipiravir in patients with liver dysfunction. 48,49 Hypersensitivity reactions, such as rashes, have been reported by 0.5% to <1% of the patients. 48 Previous studies reported that hyperuricemia was not present in the ADE database of WHO, which was used to evaluate ADEs related to favipiravir in the current study.…”
Section: Dovepressmentioning
confidence: 99%
“…Intensive care and mechanical ventilation (MV) is needed to deal with disease severity [ 6 ]. Lopinavir /Ritonavir, a HIV-1 protease inhibitor [ 7 ] has been used as a treatment option for COVID-19 as an antiviral, however, there is no clear benefit observed in the treatment of COVID-19 [ 8 ]. In contrast, remdesivir [ 9 ] and dexamethasone [ 10 ] are considered acceptable treatments with evidence for hospitalized and severe COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The luciferase activity in the supernatants was measured at the various time points after transfection. IFN-α and remdesivir have been demonstrated to inhibit SARS-CoV-2 viral infection ( Li et al, 2020 ; Wang et al, 2020a ). Daclatasvir and sofosbuvir are direct antivirals targeting hepatitis C virus NS5A ( Gao et al, 2010 ) and RNA dependent RNA polymerase ( Kohli et al, 2014 ), respectively.…”
Section: Resultsmentioning
confidence: 99%